The Recovery Time between Early Mild Stress and Final Acute Stress Affects Survival Rate, Immunity, Health, and Physiology of Oscar (Astronotus ocellatus) - Zare, Mahyar; Heidari, Elaheh; Hosseini Choupani, Seyedeh Mahsa; Akhavan, Sobhan R; Rombenso, Artur; Esmaeili, Noah (Animals, 2023)
This study investigated how the time interval between the last EMS (netting) and the acute confinement stress (AC stress) at the end of the experiment can influence growth, haematology, blood biochemistry, immunological response, antioxidant system, liver enzymes, and stress response of oscar (Astronotus ocellatus; 5.7 ± 0.8 g). Nine experimental treatments were tested, as follows: Control, Stress28 (EMS in weeks two and eight), Stress27 (EMS in weeks two and seven), Stress26 (EMS in weeks two and six), Stress25 (EMS in weeks two and five), Stress24 (EMS in week two and four), Stress23 (EMS in week two and three), Stress78 (EMS in week seven and eight), and Stress67 (EMS in week six and seven). After the nine-week experimental period, while it was not significant, fish exposed to Stress78 (26.78 g) and Stress67 (30.05 g) had the lowest growth rates. After AC stress, fish exposed to Stress78 (63.33%) and Control (60.00%) showed the lowest survival rate. The Stress78 fish displayed low resilience, illustrated by values of blood performance, LDL, total protein, lysozyme, ACH50, immunoglobin, complement component 4, complement component 3, cortisol, superoxide dismutase, catalase, and alanine aminotransferase. In conclusion, gathering consecutive stress and not enough recovery time in the Stress78 group negatively affected stress responsiveness and the health of oscar.
Keywords: stress response; antioxidant response; blood performance; blood biochemistry; stress physiology